Exploring Factors Influencing Low Birth Weight in Indonesia: Menelusuri Faktor-Faktor yang Mempengaruhi Berat Badan Lahir Rendah di Indonesia - Laili, Nisful; Widowati, Hesty (Universitas Muhammadiyah Sidoarjo, 2024)
Low birth weight (LBW) poses a considerable risk to perinatal and neonatal health, necessitating targeted interventions. However, understanding the specific factors contributing to LBW at 'Aisyiyah Siti Fatimah Tulangan Hospital remains limited. This study aimed to assess the impact of gestational age, parity, and maternal blood pressure on LBW incidence, using correlation analytics with a cross-sectional approach and a sample of 233 babies born between January and August 2023. The analysis revealed a significant association between LBW and gestational age, as well as parity, highlighting the need for proactive measures to prevent premature births and promote maternal well-being. These findings provide valuable insights for healthcare professionals and pregnant women to improve birth outcomes and reduce LBW incidence